Physical Activity of Urban-Dwelling Older People in Sri Lanka - Wickramarchchi, Bimba; Sidiah, Siop; Perera, Bilesha (2020)
There is a paucity of information on physical activity behaviour of older adults in Sri Lanka. This study determined the physical activity status of urban-dwelling older adults in a district in the country. A cross sectional survey of 880 subjects (aged 60+ years) was conducted using the Global Physical Activity Questionnaire. The prevalence rates of physically inactive, sufficiently active and highly active were 21.5%, 78.5% and 52.7% respectively. Women were more active than men (Women, 80.9% versus men, 75.5%, p < 0.05). Activity at work accounted for the highest portion of physical activity as reported by the participants [Median = 2400 MET/Week, 95% CI: 240, 4800] followed by active transport [Median =120 MET/Week, 95% CI: 0, 560] and leisure-time activity [Median = 0 MET/Week, 95% CI: 0, 270]. Factors contributing for extensively engaging activity at work need further investigations and older adults should be encouraged to do leisure-time physical activities.